1997
DOI: 10.1046/j.1365-2893.1997.00143.x
|View full text |Cite
|
Sign up to set email alerts
|

Predicted secondary structure of the hepatitis G virus and GB virus‐A 5‘ untranslated regions consistent with an internal ribosome entry site

Abstract: We describe comparative sequence analysis of 20 isolates of the recently discovered hepatitis G virus (HGV) and propose a model of the RNA secondary structure at the 3' end of the 5' untranslated region (UTR) of this virus. A single AUG starting at nucleotide position 552, which was in-frame and continuous with the putative polyprotein, was conserved in all 20 isolates and appeared to be the most likely site for the initiation of polyprotein synthesis. This consensus AUG was 14 amino acid residues upstream of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 40 publications
2
11
0
Order By: Relevance
“…In agreement with our findings from the envelope region of HGV, limited genetic variation in HGV has been reported. Studies with NS3, core and NS5a regions showed a single distribution of evolutionary distances between the isolates (Pickering et al, 1997 ;Viazov et al, 1997). Despite this other groups have suggested that HGV can be classified into genotypes or subtypes.…”
Section: Sequence Variability In the E2 Variable (Ev) Region Of Hgvmentioning
confidence: 99%
“…In agreement with our findings from the envelope region of HGV, limited genetic variation in HGV has been reported. Studies with NS3, core and NS5a regions showed a single distribution of evolutionary distances between the isolates (Pickering et al, 1997 ;Viazov et al, 1997). Despite this other groups have suggested that HGV can be classified into genotypes or subtypes.…”
Section: Sequence Variability In the E2 Variable (Ev) Region Of Hgvmentioning
confidence: 99%
“…Viruses belonging to the genus Flavivirus have a short 5ЈUTR containing a type I m 7 GpppN 1 mpN 2 cap structure (245). The 5ЈUTR of the genera Pestivirus (188) and Hepacivirus (HCV [232] and HGV [185]), however, contains an internal ribosomal entry site (IRES), which directs the ribosome to the first triplet coding for the polyprotein. Recently, it was also shown that the 3Ј end of the HCV genome enhances the efficiency of translation of the viral RNA (102).…”
Section: Viral Replication Cyclementioning
confidence: 99%
“…Therefore, co-infection of HGV with other viruses is an interesting and important subject for investigation . The reported HGV infection rates in hepatitis C patients were approximately 20% (13,14) , but a quite lower co infection rate of HGV and HCV (5.6%) was also reported (12) . HGV RNA can be found in serum for 2-20 weeks after infection.…”
Section: Introductionmentioning
confidence: 97%
“…We have attempted to determine the prevalence rate of HGV infection among healthy blood donors and blood donors with HBV or HCV infection in Kerman province, Southeast of Iran. HGV capsid protein is absent or defective and the capsid may be provided by another virus (12). Therefore, co-infection of HGV with other viruses is an interesting and important subject for investigation .…”
Section: Introductionmentioning
confidence: 99%